Harm on an innocent outsider as a lubricant of cooperation: An experiment - Christoph Engel; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2012)
If two players of a simultaneous symmetric one-shot prisoner's dilemma hold standard prefer-ences, the fact that choosing the cooperative move imposes harm on a passive outsider is imma-terial. Yet if participants hold social preferences, one might think that they are reticent to impose harm on the outsider. This is not what we find, however severe the externality. A within-subjects measure of reticence to impose harm does not explain cooperation. But the externality makes participants more pessimistic. However conditional on their beliefs participants are more, not less cooperative if cooperation entails harm on an outsider, again however severe the externality.
Keywords: C72; C91; D03; H23; 330; externality; prisoner's dilemma; modified dictator game; beliefs; Gefangenendilemma; Nichtkooperatives Spiel; Externer Effekt; Kooperation; Test